(3GdMdd aj TQM CHjGJ GdLeds - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s; (3GdRLGLj , CHh GdbGSe,J (B337 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj YdefG eG de fcf fYde bGd CHheMeO deG aQZJ ef GdcdGe aj (B"(3EUdGM GdNdd GdhGbY aj cJGH GdLed(B" s
(3BNQgG (B:s
(3hde jPcQ Cfg ddaQROb, hde CLO gPG GdHjJ ajeG WGdYJ ef TYQ GdaQROb, aCba efg Ydi MbjbI Je GdcJGH s
(3fSNI KGfjI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3HChdgG JedcGJ efgG SfI (B1091(3g``s
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs